INVENTARISASI GULMA DAN SEEDBANK PADA TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) MENGHASILKAN (TM) DI KEBUN SEI GALUH PT. PERKEBUNAN NUSANTARA V KAMPAR RIAU - Zaidan Ersyad; Ardian Ardian; Fetmi Silvina (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This study aims to inventory, to determined the composition and weed species dominancy of and to determined seedbank germination in various depth of soil in oil palm plantation. This research was conducted at Kebun Sei Galuh PT. Perkebunan Nusantara V, Kampar, Riau. This research was conducted for 3 months, starting from October 2016 until December 2016. This research used observation method. The sampling technique was done by a purposive sampling system with the criteria of land area and the age of the oil palm plant while the dominant weed species was done by vegetation analysis with quadratic methodical. The parameters observed were density (K), Relative Density (KR), Frequency (F), Relative Frequency (FR), and Importance Value Index (INP). The seedbank analysis was done by observing the growing weeds, then identified the species and counted the amount as the number of seedbank in the soil depth of 0 – 10 cm, 10 – 20 cm and 20 – 30 cm. The data that have been obtained are presented in the form of drawings, tabulated based on data groups and analyzed descriptively quantitatively, and presented descriptively qualitatively. Indicator under study in this research is planting year and weed type. The results showed that the diversity of weeds found in the crop produces palm oil consisting of 18 families and 38 species relatively the same and dominated by the family Poaceae and Cyperaceae. Dianella ensifolia, Asystasia intrusa, Eleusine indica is an important and a very dominant weed in all planted areas producing oil palm. Seedbank weeds at a depth of 0 – 10 cm has the largest number of propagules in the appeal at depths of 10 – 20 cm and 20 to 30 cm. Keywords: Inventory of weeds, Seedbank, Oil palm.